PEMBELAJARAN SEJARAH THINKING LIKE A HISTORIAN: CRITICAL READING, MIND-MAP, DAN CREATIVE WRITING - Afandi, Mahrus (Universitas Negeri Malang, 2023)
LEARNING HISTORY THINKING LIKE A HISTORIAN: CRITICAL READING,MIND-MAP, AND CREATIVE WRITING The study of history should not rely on only one source or one authoritative narrative. The natureof history which necessitates a postulate that once a historical event is written, it immediatelybecomes something subjective. It is certain that a written historical event is absolutely influencedby the subjectivity of the author. Therefore, history learning does not require a single narrative.History learning must provide opportunities for students to practice historical thinking skills thatcontain sensitivity to the multiple causes of events, empathy toward an event investigated, andsensitivity to change and continuity. This article attempts to offer a history learning model thatfacilitates students to master historical thinking skills by using activities such as critical reading,mind-map making, and creative writing. Pembelajaran sejarah tidak seharusnya hanya mengandalkan satu sumber atau satu narasi yangdianggap otoritatif. Sifat dasar sejarah yang meniscayakan adanya ketetapan bahwa ketika suatuperistiwa sejarah ditulis, maka seketika itu pula menjadi sesuatu yang subjektif, karena dipastikanpenulisan peristiwa sejarah tersebut sedikit-banyak dipengaruhi oleh subjektivitas penulisnya, itutidak menghendaki adanya narasi tunggal. Oleh karena itu, pembelajaran sejarah harus disertaidengan upaya untuk menghadirkan kesempatan bagi peserta didik untuk melatih kemampuanberpikir kesejarahan yang mengandung sensitivitas terhadap multi penyebab dari suatu peristiwa,empati terhadap konteks peristiwa yang sedang dikaji, sensitivitas terhadap perubahan, dankeberlanjutan. Artikel ini mencoba untuk menawarkan model pembelajaran sejarah yangmemfasilitasi peserta didik untuk menguasai kemampuan berpikir kesejarahan dengan memakaikegiatan seperti critical reading, pembuatan mind-map, dan creative writing.